Wish you well [videorecording (DVD)] - Baldacci, David; Burstyn, Ellen, 1932-; Foy, Mackenzie, 2000-; Martin, Darnell (Phase 4 Films, 2015)
A tragic accident forces twelve-year old Louisa Mae and her younger brother Oz to move from New York City to live with their great grandmother on a small farm in Virginia. Once Lou and Oz finally adjust to their new home, their family is threatened to be torn apart again when a coal company tries to steal their land. Now, Lou must team-up with lawyer Cotton Longfellow, to fight for their land, their home and their future.